PERSEPSI AKUNTAN DAN MAHASISWA TERHADAP EKSPEKTASI STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) - Supriyantoro, Supriyantoro (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is: (1) to find out the difference of public accountants and accounting educators perception to the expectation of financial accounting standard of entities without public accountability (2) to find out the difference of public accountants and accounting students perception to the expectation of financial accounting standard of entities without public accountability (3) to find out the difference of accounting educators and accounting students perception to the expectation of financial accounting standard of entities without public accountability. The source and type of data is the primary data which is in the form of questionnaires. The respondents are public accountants who work in public accountant office (KAP), accounting educators and accounting students who study at Indonesia School of Economic Surabaya (STIESIA) and Universitas Kristen Petra Surabaya.Based on the result of discussion, it can be concluded that: (1) there is difference of perception between public accountants and accounting educators to the expectation of financial accounting standard of entities without public accountability, (2) there is difference of perception between public accountants and accounting students to the financial accounting standard of entities without public accountability, (3) there is no difference of perception between accounting educators and accounting students to the expectation of financial accounting standard of entities without public accountability.Keywords : Perception, Financial Accounting Standard of Entities without Public Accountability, Accountant, Accounting Students